Analisis Perangkat Pembelajaran Ilmu Pengetahuan Sosial di SMP Kabupaten Jombang - Ajeng Eka Prastuti (MAN Insan Cendekia Jambi, 2024)
This study aims to determine the content analysis of the components of social studies learning devices used by teachers, the results of social studies learning devices based on the standards set in Jombang Regency. The design of this study uses quantitative descriptive content analysis consisting of 5 stages. Data collection techniques with questionnaires and documentation studies of social studies teachers in Jombang Regency. This study is based on Berelson's (1952) content analysis theory, content analysis as a research technique that studies and analyzes systematically, objectively and quantitatively the messages that appear. Researchers do not find new theories, but only implement the theory to achieve results that are in accordance with the formulation of the problem. The results of this study indicate that teachers have understood the steps of designing lesson plans along with the indicators that must be included, where this was obtained from the results of the analysis of lesson plans conducted by researchers using an item scale based on Ministerial Regulation Number 22 of 2016, the item scale based on the Ministerial Regulation can also be used as a guideline for analysis in researchers in the future, the results of the analysis of lesson plans based on the guidelines obtained the category